Beyond the screen: enhancing ethnic cultural representation and engagement through immersive 360° documentary experiences in museums - Xiaolin Sun; Eugene Ch’ng (Humanities & Social Sciences Communications)
Abstract In this era of digital heritage, immersive media, such as 360° documentaries, have been proposed to enrich engagement and learning. However, how immersive 360° media formats influence the understanding of ethnic minority cultures remains underexplored. We conducted a controlled laboratory experiment comparing traditional 2D and 360° documentary presentations of the Miao community in Guizhou Province, using the same narration and content, including village scenes, performances, and crafts, to isolate the effect of media format. The results suggest that the 360° documentary may increase viewers’ enjoyment, sense of presence, curiosity, and appreciation of cultural content relative to a comparable 2D film. These exploratory findings indicate a potential for immersive media to deepen cultural understanding. Our study underscores 360° documentaries as a promising tool for engaging audiences with ethnic minority cultures, while noting that these conclusions are provisional given the lab setting and should be tested in real-world museum contexts.